2013
DOI: 10.2478/s13540-013-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

The M-Wright function as a generalization of the Gaussian density for fractional diffusion processes

Abstract: The leading role of a special function of the Wright-type, referred to as M-Wright or Mainardi function, within a parametric class of self-similar stochastic processes with stationary increments, is surveyed. This class of processes, known as generalized grey Brownian motion, provides models for both fast and slow anomalous diffusion. In view of a subordination-type formula involving M-Wright functions, these processes emerge to have all finite moments and be uniquely defined by their mean and auto-covariance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…It is also referred to as M-Wright/Mainardi function because it was originally obtained by Mainardi as the fundamental solution of the time-fractional diffusion equation [32]. It has been shown that when such fractional diffusion processes are properly characterized with stationary increments, the M-Wright/Mainardi function plays the same key role as the Gaussian density for the standard and fractional Brownian motions [33,34]. The properties of the corresponding master equation lead to such diffusion processes being named as Erdélyi-Kober fractional diffusion [35,36].…”
Section: "To Us Complexity Means That We Have Structure With Variatimentioning
confidence: 99%
“…It is also referred to as M-Wright/Mainardi function because it was originally obtained by Mainardi as the fundamental solution of the time-fractional diffusion equation [32]. It has been shown that when such fractional diffusion processes are properly characterized with stationary increments, the M-Wright/Mainardi function plays the same key role as the Gaussian density for the standard and fractional Brownian motions [33,34]. The properties of the corresponding master equation lead to such diffusion processes being named as Erdélyi-Kober fractional diffusion [35,36].…”
Section: "To Us Complexity Means That We Have Structure With Variatimentioning
confidence: 99%
“…What concerns particle displacement PDFs, they generally are not Gaussian [45] and mainly characterized by the decay of their tails. In particular, the PDF related to the time-fractional diffusion equation is a M-Wright/Mainardi [49], [50] density that is unimodal (diffusive) and bimodal (wave-like behaviour) in subdiffusion and superdiffusion cases, respectively. In subdiffusion cases, tails decay with a stretched exponential that is fatter than the Gaussian and in superdiffusion cases with a stretched exponential that is thinner than the Gaussian.…”
Section: Introductionmentioning
confidence: 99%
“…In this subsection, we shortly discuss the special functions of the Wright type that appear in these derivations. For more details regarding theory and applications of these special functions, we refer the reader to, for example, [30][31][32][33][34][35][36].…”
Section: Special Functions Of the Wright Typementioning
confidence: 99%